PENGARUH KETERAMPILAN MEMBUKA PELAJARAN TERHADAP MOTIVASI SISWA DALAM BELAJAR BAHASA INDONESIA SEKOLAH DASAR - Asria Azis (Journal of Educational Science and Technology (EST), 2016)
The objective this research was to describe: 1) teacher ability on Bahasa Indonesia learning process using opening learning skill, 2) student activities on opening learning skill process, 3) student motivation on Bahasa Indonesia learning process before and after implementation of opening learning skill in experiment group, 4) student motivation on Bahasa Indonesia learning process before and after learning process without implementation of opening learning skill, 5) to find out the influence of teaching skill in opening learning toward student motivation on studying Bahasa Indonesia. The method used was true experiment with pre-test post-test control group design. The population in the study are 5th grade student at SDN 139 Inpres Lambatorang in Bantimurung District Maros Regency. Samples used are 30 student, 15 student each from experiment and comparing group. The data was collective by test and observation, the data obtained from samples were analyzed by descritive and inferensial statistic. The result shows: 1) teacher ability on Bahasa Indonesia learning process use opening learning skill have increased, 2) student activities on Bahasa Indonesia learning process use opening learning skill have increased, 3) student learning motivation who teached by opening learning skill have increased, 4) student learning motivation who teached without opening learning skill have not increased, 5) opening learning skill influencing toward Student Motivation on Studying Bahasa Indonesia